1988
DOI: 10.1051/rnd:19880705
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation of sheep ovarian oocytes

Abstract: Summary. An in vitro system has been developed which induces full meiotic maturation in 98 % ovarian sheep oocytes isolated from follicles 2-6 mm in diameter. 45.7 % of these were fertilized, determined by the presence of two pronuclei, extrusion of the second polar body and the presence of the sperm flagellum.This culture system was used to describe the morphological changes during meiotic maturation, examining the nucleus, the cytoplasm and cumulus (corona)-oocyte relationship. 24 h are required for maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
5
8
0
Order By: Relevance
“…In previous experiments of in vitro maturation (IVM) of sheep oocytes, we have shown that, after 6-7 h of culture in the presence of gonadotropins, dispersion of the cumulus and a progressive retraction of FP occurred. The dissociation of the intercellular junctions began concomitantly with germinal vesicle breakdown (GVBD) (Szollosi et al, 1988). Similar observations have been reported by Hyttel et al (1986).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In previous experiments of in vitro maturation (IVM) of sheep oocytes, we have shown that, after 6-7 h of culture in the presence of gonadotropins, dispersion of the cumulus and a progressive retraction of FP occurred. The dissociation of the intercellular junctions began concomitantly with germinal vesicle breakdown (GVBD) (Szollosi et al, 1988). Similar observations have been reported by Hyttel et al (1986).…”
Section: Introductionsupporting
confidence: 77%
“…Electron microscopy (EM). COCs were fixed and prepared following the procedure employed and reported previously (Szollosi et al, 1988).…”
Section: Cytological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of these events is accompanied by changes in the phosphor- 1 Supported by the Ministero dell'Università e Ricerca Scientifica e Tecnologica (project ex 40%). 2 Correspondence: Sergio Ledda, Department of Animal Biology, University of Sassari, V. Vienna ylation patterns of various cellular proteins [6,7] and structural modification [8,9]. Meiotic progression is regulated by the activity of the maturation-promoting factor (MPF), the universal cell cycle regulator of both mitosis and meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…This question can be most easily addressed using a physiologically relevant in vitro maturation (IVM) system that allows ovine oocytes and their companion somatic cells to progress through all the biological checkpoints and signalling events required to facilitate oocyte meiotic progression and cumulus mucification and expansion in vivo. Many approaches have been used to support the IVM of oocytes that impact on the mechanism of initiation of oocyte maturation in vitro and the length of time in culture (24-48 h) from a range of species including mouse (De la Fuente et al 1999), cow (Brum et al 2005) and sheep (Szollosi et al 1988). Meiotic progression can occur spontaneously (Hartshorne et al 1994), or be induced by the removal of COCs from the follicle (Leonardsen et al 2000, Nogueira et al 2005 or by the disconnection of oocytes from their cumulus cells (Pincus & Enzmann 1935).…”
Section: Introductionmentioning
confidence: 99%